Apakah Manajemen Laba dilakukan untuk Tax Planning atau untuk Menjadikan Laba Lebih Persisten? - Sari, Martdian Ratna; Pinasthika, Benediktus Tandya (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to examine how the company's earnings management affects the amount of tax and earnings persistence, especially in the transportation business in Indonesia. This research is important because the Financial Accounting Standards Guidelines (PSAK) do not regulate the limits in managing earnings so that it can lead to various potential fraud that ultimately violates the PSAK and the Laws Regulations relating to the presentation of financial statements. This study uses a transportation company as a sample, with 70 observations of total financial data during 2014-2018, a span of 5 years. The results of this study prove that earnings management does not affect tax planning and earnings persistence due to the profit recognition method of each different company. The role of the agent is the key to persistent earnings as a signal to the principal. From the results of this study, researchers suspect that the real activity of companies represents the condition of earnings and the method of recognition has no relationship with earnings persistence. The author suspects that the company cannot do earnings management and tax planning simultaneously.